2013
DOI: 10.1523/jneurosci.1119-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Mitochondrial Calcium Buffering Capacity Reduces Aggregation of Misfolded SOD1 and Motor Neuron Cell Death without Extending Survival in Mouse Models of Inherited Amyotrophic Lateral Sclerosis

Abstract: Mitochondria have been proposed as targets for toxicity in amyotrophic lateral sclerosis (ALS), a progressive, fatal adult-onset neurodegenerative disorder characterized by the selective loss of motor neurons. A decrease in the capacity of spinal cord mitochondria to buffer calcium (Ca2+) has been observed in mice expressing ALS linked mutants of SOD1 that develop motor neuron disease with many of the key pathological hallmarks seen in ALS patients. In mice expressing three different ALS-causing SOD1 mutants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 96 publications
11
117
0
Order By: Relevance
“…Approximately 10% of all of the gene changes are in this category, consistent with synapse dysfunction accompanying the known denervation that occurs as one of the earliest detected changes in this mouse line (34). Up-regulated gene changes were enriched in genes involved in metabolism, with notable perturbation in the alanine, aspartate, and glutamate metabolism pathways (marked with red stars and red shade in SI Appendix, Fig.…”
Section: Activation Of Er Stress In Motor Neurons Expressing Mutant Smentioning
confidence: 52%
“…Approximately 10% of all of the gene changes are in this category, consistent with synapse dysfunction accompanying the known denervation that occurs as one of the earliest detected changes in this mouse line (34). Up-regulated gene changes were enriched in genes involved in metabolism, with notable perturbation in the alanine, aspartate, and glutamate metabolism pathways (marked with red stars and red shade in SI Appendix, Fig.…”
Section: Activation Of Er Stress In Motor Neurons Expressing Mutant Smentioning
confidence: 52%
“…Of note, a previous study has shown that reducing the levels of aggregated misfolded SOD1 by deleting cyclophilin D does not ameliorate the pathogenesis of ALS in mutant SOD1 mouse models (32). Therefore, SOD1 toxicity in vivo appears to derive from the soluble form of the misfolded SOD1, rather than from its highly aggregated form.…”
Section: Discussionmentioning
confidence: 93%
“…Prolonged openings cause mitochondrial depolarization, osmotic swelling, outer mitochondrial membrane rupture, and release of apoptogenic proteins such as cytochrome c; transient openings, on the other hand, may be involved in physiological Ca 2ϩ homeostasis and may protect mitochondria from Ca 2ϩ overload (10,11), as indicated by studies in isolated cardiomyocytes, CyPD knock-out mice, adult cortical neurons, and spinal chord mitochondria (51)(52)(53)(54). It is tempting to speculate that the different PTP conductances observed in mammals, Drosophila, and yeast underscore different physiological functions.…”
Section: Bottom Left Panel); and (Ii) By Colocalization With Mitotracmentioning
confidence: 99%